Examining the effects of cognitive training on levels of executive function in adults with down syndrome: A feasibility study - MCGLINCHEY, EIMEAR (Trinity College Dublin. School of Nursing & Midwifery. Discipline of Nursing, 2017)
Introduction Individuals with Down syndrome are at much greater risk of developing AD, and one of the early clinical symptoms of AD is executive dysfunction. In the general population, cognitive training has shown some promising results in relation to maintaining or improving cognitive processes. There is currently a gap in the literature in relation to cognitive training for adults with DS. Aims The aim of the study is to assess the feasibility of using a cognitive training program with adults with Down syndrome and to examine the influence of training on levels of executive function in this population. Method A quasi-experimental mixed factorial design with partial crossover was used involving an eight week intervention period using a brain training program. Participants were matched on age and then randomly assigned to either the treatment group or the delayed control group. Forty adults with Down syndrome, aged between 30 and 49 and with a mild or moderate level of intellectual disability participated in the study. All participants completed baseline measures of executive function, using both neuropsychological assessments and a proxy rated measure of behavioural executive function. The active group first completed then training and then the delayed control group. Executive function assessments were repeated for both groups following the training. Results Based on a number of parameters to determine feasibility, from the point of view of both the person with DS and those caring for the person with DS, it was found that it was feasible to conduct such a program. The study also aimed to examine whether a cognitive training program could have an effect on levels of executive function. While, conclusions are limited due to small sample size, improvement was seen in neuropsychological assessments of executive function following cognitive training. Positive effects reflected in everyday behaviours were not as promising. These findings need further investigation with a larger sample size.
APPROVED
Keywords: Down syndrome; Cognitive Training; Alzheimer's; Dementia; Executive Function; Intervention